Bilateral nonarteritic anterior ischemic neuropathy following acute angle-closure glaucoma in a patient with iridoschisis: case report - Torricelli,André (2011)
A 55-year-old woman was referred to our clinic because of a one-week history of visual loss and raised intraocular pressure in the left eye followed 4 days later by visual loss in the right eye. Slit-lamp examination showed bilateral conjunctival hyperemia, slight diffuse corneal edema, shallow anterior chamber and fixed and dilated pupil in both eyes. Splitting of the anterior layers of the iris with fibrillar degeneration extending for approximately one quadrant inferiorly was presented in each eye. Fundus examination showed opitc disc edema with no vascular tortuosity and no cup in both eyes. The condition was treated as bilateral acute angle-closure glaucoma in a patient with irisdoschisis. After medical treatment and improvement of visual acuity, perimetry revealed a significant visual field defect especially in left eye; this case represents a rare concurrence of acute angle-closure glaucoma and bilateral nonarteritic ischemic optic neuropathy. Although most cases of elevated intraocular pressure, including acute angle-closure glaucoma, do not result in optic disc edema and irreversible vision loss, variations in the vascular supply of the nerve optic head along with others ocular systemic risk factors, may predispose certain individuals to nonarteritic ischemic optic neuropathy during periods of elevated intraocular pressure.